Sosialisasi dan Pemasangan Sistem Penerangan Berbasis Tenaga Surya Di Panti Asuhan Mekar Sari - Darmawan, Marten; Soewono, Arka Dwinanda; Hutagalung, Rory Anthony; Christiand, Christiand; Fanlau, Dylan Ryo (Jurnal Pengabdian Masyarakat Charitas, 2022)
Solar energy is one of the sustainable and environmentally friendly energy sources. However, this renewable energy is still not widely utilized by the people of Indonesia even though Indonesia, as a tropical country, has vast solar energy potential. Hence, It is essential to introduce and socialize solar energy potential to the general public. The partner of this community outreach program is Mekar Lestari Orphanage in South Tangerang. The orphanage care for children aged 3-16 years from various backgrounds. As a younger generation, it is hopeful that they can develop a mindset of solar energy as one of the renewable energy sources that can replace fossil fuels. In addition, the Mekar Lestari Orphanage in its social role requires a facility with adequate lighting. However, there was a lack of lighting in the front yard of the orphanage, making access to the facility difficult, especially at night. Therefore, a solar energy-based lighting system has been built and installed on the front gate of the orphanage. After installing the lighting system, socialization about the basic theory of solar energy and how the solar-powered lighting system works was conducted. The evaluation of the event, attended by representatives of staff and children living in the orphanage, showed that all participants gained new knowledge and a deeper understanding of solar energy. In addition, they learned new skills to operate and maintain solar lighting systems. From the positive feedback during the socialization, it is hopeful that this activity can provide education on the actual application of solar energy and help to improve lighting conditions in the orphanage.